Implementation of hentian komuniti towards heritage town sustainability / Yong Adilah Shamsul Harumain ... [et al.] - Yong Adilah, Shamsul Harumain; Nikmatul Adha, Nordin; Nur Farhana, Azmi; Morimoto, Akinori; Teppe, Osada (Universiti Teknologi MARA, Perak, 2019)
The sustainability of heritage town has been a huge controversial issue. Many local authorities struggle to sustain heritage buildings due to lack of community participation although they have adequate funding. As a result, many guidelines or even restrictions to sustain those building meets a dead end. Most heritage building owners also face issues in maintaining their buildings due to the building age and change of use. Other challenges are cost, value and also interest. Community participation in the process of sustaining heritage towns is equally important with the vital needs of the local authority to maintained them. Both work together as a complete system that compliments each other. The Hentian Komuniti is a unique community participation concept which is a translation of a concept called Machinoeki from Japan that reflects hospitality and volunteerism. The core principal of Hentian Komuniti concept is to encourage the community to share the space at their building premises where visitors can rest, get information about the town, and also use the toilet service for free. This is an interesting concept as the community works voluntarily to help the local government to revitalize the town, nurture the idea of hospitality, which means cultivate and educate good services. This paper explains the implementation of this concept in the town of Taiping and the chain benefit outcome from the surveys undertaken towards heritage building owners and local community in the effort to sustain the heritage town.